2021
DOI: 10.1177/10556656211050004
|View full text |Cite
|
Sign up to set email alerts
|

The Panorama of Cleft Lip and Palate Live Birth in Brazil: Follow-up of a 10-Year Period and Inequalities in the Health System

Abstract: Objective To provide the prevalence and an overview of cleft lip and palate (CL/P) in the period of 2008 to 2017, as well as the profile of care provided for this condition in Brazil. Design Cross-sectional study of epidemiological character. Setting Brazilian government website. Participants National Live Birth and Hospital Information System. Intervention Organization of the end databases and performance-based statistical analysis. Main Outcome Measure(s) Analysis of the prevalence of CL/P in newborns, socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…In all of these studies the prevalence of OC showed differences between the Federative Units and the regions. The overall prevalence of OC in Brazil found in this present study is in accordance with what was found in the literature regarding the country; 6 8 , 28 , 29 however, the Brazilian prevalence of this malformation is lower than the global, which is about 1–1.5/1,000 live births. 3 Some reasons that could explain it are the underestimation of reported cases of OC in the national system, and the misdiagnosis of clefs in some Brazilian regions, especially those with the lowest reports.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In all of these studies the prevalence of OC showed differences between the Federative Units and the regions. The overall prevalence of OC in Brazil found in this present study is in accordance with what was found in the literature regarding the country; 6 8 , 28 , 29 however, the Brazilian prevalence of this malformation is lower than the global, which is about 1–1.5/1,000 live births. 3 Some reasons that could explain it are the underestimation of reported cases of OC in the national system, and the misdiagnosis of clefs in some Brazilian regions, especially those with the lowest reports.…”
Section: Discussionsupporting
confidence: 92%
“…Studies done involving the years between 2009 and 2013 found prevalences ranging from 4.85/10,000 live births 29 to 5.86/10,000 live births. 28 The most recent ones 7 , 8 found prevalences near 5.1/10,000 live births for the 2005–2017 period. In all of these studies the prevalence of OC showed differences between the Federative Units and the regions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations